Integrated Reporting: “The Road Traveled So Far, Where It Stands, and Where It is Heading" - Mushtaq, Syed Asif; Kawoosa, Lubna Afzal (Research in Accounting Journal (RAJ), 2024)
This study provides a comprehensive exploration of Integrated Reporting (IR), examining its origins, current adoption trends, and future trajectories as a response to the limitations of traditional financial reporting. By integrating financial and non-financial data, IR aims to offer a holistic view of organizational performance, emphasizing connectivity, materiality, and stakeholder engagement. Despite its theoretical promise, IR faces implementation challenges, including conceptual ambiguity, inconsistent adoption, and the non-binding nature of frameworks like the International Integrated Reporting Council (IIRC). The study employs a qualitative, exploratory-descriptive methodology, analyzing secondary data from peer-reviewed literature, institutional reports, and regulatory documents to map global IR adoption patterns. Findings reveal significant regional disparities, with the Asia Pacific leading in adoption (42.1%), followed by the Middle East & Africa (27.1%) and Europe (25.1%). Recent developments, such as the merger of the IIRC and the Sustainability Accounting Standards Board (SASB) into the Value Reporting Foundation (VRF) and the creation of the International Sustainability Standards Board (ISSB), highlight IR’s evolving role in global sustainability reporting. While IR enhances transparency and long-term value creation, its success hinges on addressing stakeholder inclusivity, standardizing materiality assessments, and fostering collaboration among regulators, investors, and corporations. The study concludes that IR represents a progressive shift in corporate reporting but requires clearer guidance and broader institutional support to realize its full potential as a tool for sustainable business practices.